Combination of modified bentall procedure and orthotopic liver transplantation - Seppelt, Philipp; Haken, Rebecca von; Werner, Jens; Kallenbach, Klaus (Case reports in transplantation, 2018)
Indication for combined cardiac surgery and orthotopic liver transplantation is rare and patients are at high risks. Individual surgical strategy must be developed since a general standard of such procedure does not exist. We report the case of a 45-year-old woman who underwent simultaneously modified Bentall procedure and orthotopic liver transplantation. Underlying diseases were end-stage polycystic liver, aneurysm of the ascending aorta, and severe aortic regurgitation. To avoid prolonged bypass times, both teams worked simultaneously. During cardiac reperfusion, time inferior vena cava stayed ligated while the cyst liver was explanted.
Gesehen am 25.09.2019